Corrosion of potential first stage blade materials in simulated supercritical CO2 - Norman, Boma Phoebe; Al Baroudi, Hisham; Potter, Andrew; Mori, Stefano; Simms, Nigel J.; Kulkarni, Anand; Sumner, Joy (Taylor and Francis, 2023)
Global power consumption is predicted to double by 2050, notably driven by the transportation and energy sectors necessitating limitations of emissions. Due to its compact turbomachinery, better thermal efficiency, and simpler layout, supercritical-CO2 cycles have received attention, with numerous variations proposed (either indirect-fired/closed cycles or direct-fired-open cycles). One technical challenge is degradation pathway quantification of turbine materials in sCO2 as selection is crucial to successfully and economically operate new plants. This requires degradation assessment in representative environments simulating the Allam cycle. Laboratory tests were conducted on a first stage turbine blade alloy, CM247, with either an environmentally resistant coating or bond coat/thermal barrier coat at one atmosphere and 800°C, with potential exposure including (O2, H2O, N2, SO2) for up to 1000 h. Weight change and metallographic measurements tracked scale development. Scanning electron microscopy/energy dispersive X-ray spectroscopy studied scales and internal precipitates. Locations of contaminant element in the CO2-rich environment were investigated.
Keywords: sCO2; nickel-based alloy; Allam cycle